RELIGIOUS MODERATION IN THE CONTEXT OF ISLAMIC EDUCATION: A MULTIDISCIPLINARY PERSPECTIVE AND ITS APPLICATION IN ISLAMIC EDUCATIONAL INSTITUTIONS IN INDONESIA - Rahmadi Rahmadi; Hamdan Hamdan (UIN Antasari Banjarmasin, 2023)
This research explores the multifaceted concept of religious moderation within the context of Islamic education in Indonesia. The study investigates four primary aspects: the foundational idea of religious moderation, its diverse perspectives and approaches, the implications of religious moderation in education, and its practical implementation in Islamic educational institutions. Various perspectives on religious moderation education, including theological-normative, sociological, anthropological, and cross-cultural communication perspectives, are examined in detail. Normatively, religious moderation education is guided by the concept of